ENGLISH COMMUNICATION NEEDS ANALYSIS OF THE OJEK ONLINE DRIVERS COMMUNITY IN BANYUWANGI REGENCY - Abdul Halim; Sutami Dwi Lestari (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Online motorcycle taxi is a transportation mode that is also developing in the Banyuwangi regency. The development of regional tourism is the potential for foreign tourists as users of the services. This study aims to analyze the need for communication in English among online motorcycle taxi drivers in Banyuwangi . The study was conducted with a direct survey of 20 male drivers. The selection of respondents was done by using the snow ball method. Data were collected by means of a questionnaire containing 7 questions, each of which has 4 answer choices. Questionnaire data are grouped according to answers and analyzed according to existing theories. The results showed that online motorcycle taxi drivers need to improve communication skills in English for services to foreign tourists.